Industry-Based Misconceptions Regarding Cross-Pollination of Cannabis spp. - Olejar, Kenneth J.; Park, Sang-Hyuck (Frontiers in Plant Science, 2022)
Cross-pollination of commercial crops has been an ongoing issue in many species. Cannabis spp. encompasses the classifications of marijuana [high in Δ9-tetrahydrocannabinol (THC)] and hemp (below 0.3% THC). As such, cannabis is the most recent crop facing the dilemma of cross-pollination and is leading to litigation. These litigations are driven by the large misunderstanding of the impacts of cross-pollination within the cannabis industry. The misconception is that if hemp is cross-pollinated by high THC cannabis, the hemp will become “hot” (high in THC) thereby rendering the crop illegal under the 2018 Farm Bill. However, there are many factors that contribute to the amount of THC a plant may produce. This article examines and refutes the misconception of cross-pollination increasing THC levels by highlighting several methods of how THC may become high in a given hemp crop.